ChemInform Abstract: Silver‐Catalyzed Vinylogous Fluorination of Vinyl Diazoacetates. Issue 22 (3rd June 2014) - Qin, Changming; Davies, Huw M. L.
Abstract The method can be extended to preparation of more complex compounds like fluorinated farnesol as well as 6‐β‐fluoro‐steroid derivatives.